The relationship between academic procrastination, academic stress, and life happiness of Mahmud Yunus Batusangkar State Islamic University students - Fitriani, Wahidah; Sabrial, Jumli (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
This research aimed to examine the relationship between academic procrastination, academic stress, and life happiness of UIN Mahmud Yunus Batusangkar students. The method employed in this research was the correlational research method. The research population was 110 students in semesters 1 to 8 with high levels of academic procrastination and high academic stress. The data collection technique used a self-report questionnaire and it used a questionnaire as research instrument. The online Google form media was a data collection tool. The Likert scale was the assessment system used in this study. Multiple regression analysis wasthe data analysis technique, by using the SPSS 25 program in the data analysis stage. (R2) was observed in the multiple linear regression test with a range of 0 to 1. From the analysis, R2 had a range of 0.676. The conclusion of the correlation research between academic procrastination, academic stress, and life happiness of UIN Mahmud Yunus Batusangkar students wassignificant and concrete, expressed through the results of the statistical program for social science R of 0.676.